Antimicrobial effect of three essential oils from the Lamiaceae family for control Ralstonia solanacearum - Acero-Godoy, Jovanna (2025)
Rosmarinus officinalis L., Origanum majorana L., and Thymus vulgaris L. are aromatic plants that belong to the Lamiaceae family. Their essential oils have been widely studied as antimicrobials against phytopathogenic bacteria, including R. solanacearum. The objective of the present investigation was to determine the chemical composition of essential oils and the antimicrobial activity against R. solanacearum. The essential oils were obtained from leaves and stems by Steam distillation method, and chemical composition was determined using CG-MS; Minimum inhibitory concentration (MIC) and minimum bactericidal concentration tests were developed for each essential oil. Most found compounds for O. majorana and T. vulgaris were γ-terpinene 17,32 %, and 33,47 % respectively for R. officinalis α-pinene 22,47 %. The average density of three essential oils was 0,85 mg/mL, and the highest essential oil (EO) yield was obtained for R. officinalis 0,86 % (% w/w). All essential oils generated both inhibitory and bactericidal effects against R. solanacearum: for O. majorana, T. vulgaris, and R. officinalis the MIC were 0,545 mg/mL, 0,625 mg/mL, and 1,09 mg/mL respectively and the MBC value was 1,09 mg/mL, 1,25 mg/mL and 2,18 mg/mL respectively. These results allow us to propose using essential oils as biopesticides as an alternative to reduce the application of conventional synthetic chemicals, mitigating the impact that these produce on water, soil, and the final consumer, humans.